Evaluasi Penerimaan Kas Terhadap Pendapatan Pada PT.Suryagita Nusaraya Cargo Cabang Maumere - Emilianus Eo Kutu Goo; Maria Nona Dince; Walter Obon; Magdalena Samosir; Yoseph Darius Purnama Rangga (COSTING : Journal of Economic, Business and Accounting, 2020)
An accounting information system is a collection of various resources, both human and equipment, which are specially designed to assist processing to convert financial data and other data into information. This study aims to determine whether the accounting information system for cash receipts for package delivery revenue at PT.Suryagita Nusaraya is adequate. The analytical method used is descriptive qualitative method. Research data obtained from interviews, observation and documentation. The results showed that the functions, documents, accounting records, and cash receipts accounting information system procedures were still inadequate. The existing functions are based on theory, but in carrying out their functions there is no separation of duties. The documents used are incomplete because the company did not make a packing slip. Accounting records and cash receipt procedures have been implemented properly. The results also show that the main elements of internal control that support the cash receipt process have not been implemented properly. Keywords: Accounting Information Systems, Cash Receipts